ARTIFICIAL INTELLIGENCE IN THE SYSTEM OF DETERMINANT OF THE MODERN BUSINESS COMPETITIVENESS - BARABAS, Dmytro; ILNYTSKYY, Denys; ANDRUSYK, Vladyslav (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The work is devoted to the systematization of scientific achievements in the field of using the potential of digital technologies to manage the competitiveness of modern business. The article considers the prerequisites for the spread of the use of artificial intelligence in the activities of companies. Examples of effective implementation of artificial intelligence tools for the formation of competitive advantages of business are given. Productive ways of using artificial intelligence to improve knowledge management and save time are summarized. The information, time and technological dimensions of the competitiveness of modern business are studied. It is argued that business organizations, thanks to the large-scale use of artificial intelligence, are able to form competitive advantages based on the simultaneous improvement of knowledge and time management. For customers, the time saving is even more significant due to the acceleration of processing of their requests, personalized recommendations, optimization of service processes through the automation of financial operations and internal business processes. The range of AI tools useful not only for large corporations but also for small businesses is considered. The importance of a powerful hardware base for the functioning of artificial intelligence is highlighted, in which semiconductor technologies play a key role. Innovations in semiconductors enable artificial intelligence to function and expand, which, in turn, helps companies achieve competitive advantages. A new generation of developed semiconductor chips, including graphics processors, specialized chips, and neuromorphic chips, allows companies to achieve significant improvements in the efficiency of their intelligent systems. The prospects for the use of quantum technologies in the near future are outlined.
Keywords: competitive paradigm; knowledge; competitive advantage; technological development; new industrialization; smartization; business